The Influence of Employee Participation on Managerial Performance in Budget Preparation - Marshelina, Saragi (CV. Rayyan Dwi Bharata, 2024)
Preparing a good budget should use bottom-up principles involving various levels of positions in each department in a company. This will be better because you can expect various input from subordinates to determine the performance targets you want to achieve in a certain period or time period. Pirngadi Hospital is a Government General Hospital in the city of Ambon. Managing Health Equipment Expenditures requires an appropriate budget in terms of planning and use. Cases of reusing or recycling medical equipment or using reconditioned medical equipment in 2023 indicate that budget management is not being used appropriately. Without organizational commitment, participation will have no effect on managerial performance. Participation with influential commitment will improve managerial performance. The system of organizational commitment and giving rewards to parties involved in preparing the budget is quite interesting. The sample was selected using the Census method, where 32 people were selected from the sample members who were in the operations and purchasing of health equipment. Pirngadi Ambon General Hospital was all taken for survey. This was done because of the limitations of the sample taken so that the entire Operations (Engineering) and equipment purchasing (planning) sections were taken which were directly involved in planning and budget preparation. Data were processed using SPSS version 17 software with a linear regression method using moderating variables. Data analysis was carried out using a regression approach using moderating variables with an alpha level of 0.05 (5%) meaning below 0.05 (t-value 0.05) so each variable has a significant effect. Partial correlation testing using the t-test shows that the organizational commitment variable has an influence on the relationship between participation in budget preparation and managerial performance. Simultaneous testing is carried out with the F-test (F-value 0.05) or 0.000, so all variables together have a significant effect. The results show that there is a simultaneous influence of organizational commitment and rewards on the relationship between participation in budget preparation and managerial performance.